2015
DOI: 10.1167/iovs.14-16345
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Damage in Progressive Hydroxychloroquine Retinopathy On and Off the Drug: Inner Versus Outer Retina, Parafovea Versus Peripheral Fovea

Abstract: Hydroxychloroquine retinopathy primarily involves outer retina (photoreceptors). Outer retinal thinning while using HCQ initially involves the parafovea, but becomes diffuse across the macula as damage progresses or after drug cessation. When HCQ is stopped at an early or moderate stage (before RPE damage), progression seems to be limited to the first year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
97
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 13 publications
5
97
1
Order By: Relevance
“…19 Spectral-domain optical coherence tomography images show localized thinning of retinal layers in the parafoveal zone, and may reveal retinal toxicity at an earlier stage before visual field loss occurs. 6,11,[20][21][22] Majority of the previous studies were related to the pathologies associated with the outer retinal segment involving retinal pigment epithelium and photoreceptors. 13,21,23 However, some other studies also demonstrated HCQassociated damage in the inner retinal segment.…”
Section: Discussionmentioning
confidence: 99%
“…19 Spectral-domain optical coherence tomography images show localized thinning of retinal layers in the parafoveal zone, and may reveal retinal toxicity at an earlier stage before visual field loss occurs. 6,11,[20][21][22] Majority of the previous studies were related to the pathologies associated with the outer retinal segment involving retinal pigment epithelium and photoreceptors. 13,21,23 However, some other studies also demonstrated HCQassociated damage in the inner retinal segment.…”
Section: Discussionmentioning
confidence: 99%
“…A reliable automated segmentation approach, such as that presented herein, is crucial to enabling such work. Our work has also shown superior results to other state-of-the-art clinical software in eyes affected by hydroxychloroquine toxicity [15] and post-surgical macular hole eyes [6]. We plan to expand our segmentation method to SD-OCT scans acquired in the region surrounding the optic disc as well as to eyes presenting with other retinal pathologies, such as glaucoma and retinitis pigmentosa.…”
Section: Discussionmentioning
confidence: 90%
“…Our method is sought to address the aforementioned challenges of prior algorithms, producing accurate delineations of the intraretinal layered structure in scans acquired during clinical practice and maintaining a stable behavior in disease cases while also producing accurate outlines that follow the particular pathologies of the disease, not smoothing out important details. This method was used previously for the segmentation of the retina in hydroxychloroquine toxicity [15] and postsurgery in macular hole cases [6]. In these applications, the results of our methods were successful and superior to current commercial software by visual inspection, but details about the method and its evaluation have not yet been published.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations